COMPARISON STUDY OF CORROSION RATE MODEL FOR TUBULAR GOODS SELECTION OPTIMIZATION IN CARBON CAPTURE STORAGE APPLICATION - Baravanni, Afdhal
Continuous-growth of demand for energy from conventional fossil fuels causes escalation in the emission of carbon dioxide (CO2), which is a factor that can lead to climate change and global warming. Carbon Capture Storage (CCS) collects and stores CO2 into pores of rock formations below the surface. Moreover, CO2 is easily dissolved in water and reacted with metal surfaces. Therefore, it can cause a corrosion problem in casing and tubing of injection well. An existing temporary abandoned exploration well is decided as a candidate for CO2 injection well in Field X to be applied with CCS technology. The main aim of this study is to predict the corrosion rate model by using Electronic Corrosion Engineer (ECETM) software. Arimbawa (2013) created a new integrated analysis to determine the maximum corrosion rate of gas wells by considering reservoir condition, nodal analysis, and well trajectory. Meanwhile, Fadholi (2014) developed model of a corrosion rate prediction on tubing based on prior model of Lianne Smith, Mike Billingham and C de Waard. This study is continuation from previous studies which focuses on corrosion rate prediction model comparison between an existing abandoned exploration well in Field X and a CO2 injection well on CCS demonstration project located in Tomakomai, Japan, based on literature study. The corrosion rate model is evaluated using NORSOK (Norwegian offshore sector) M-001 standard. This comparative study can be used to select the best tubular goods to be applied in CO2 injection wells for CCS application which will eventually prolong the lifetime of tubing strings. As a result, Corrosion Resistance Alloy (CRA) material tubing is required to be applied to the candidate for CO2 injection well in Field X. Furthermore, this study provides recommendation for changing the tubing size of CO2 injection well in Tomakomai CCS demonstration project.